«Վահագնի երգը» և հայկական էպոսը Նոր տեսակետ հայկական էպոսի ծագման և ձևավորման վերաբերյալ - Պետրոսյան, Արմեն (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Многократные повторы звукосочетания erk в древнеармянском гимне о рождении бога грозы и войны Вахагна рассматриваются в качестве анаграммы слова erku «два» с аллюзией на двойственность. А в выражении cov cirani «пурпурное море» можно увидеть анаграмму имени Covinar, матери эпических близнецов Санасара и Багдасара, первых героев эпоса «Сасунские безумцы» (мифологической персонификации пурпурного небесного моря). Образ Санасара, старшего близнеца, основоположника рода героев, восходит к Вахагну. Та же картина рождения мифологических близнецов повторяется и в эпосе «Випасанк». Multiple recurrences of the sound combination erk- in the ancient Armenian hymn on the birth of Vahagn, the god of thunder and war, can be considered an anagram of the word erku (two) with an allusion to twins. Moreover, in the expression cov cirani (purple sea) one can see an anagram of Covinar, the name of the mother of the epic twins Sanasar and Baghdasar, first heroes of the epic "Daredevils of Sassoun". In this context it becomes obvious that the image of Sanasar, the elder of the twins, founder of the dynasty of heroes, directly goes back to Vahagn. The same picture of the birth of mythological twins occurs in the ancient epic “Vipasank”.
Keywords: Բանասիրություն